Simulating impacts of irrigation heterogeneity on onion (Allium cepa L.) yield in a humid climate - Pérez-Ortolá, Marta; Daccache, Andre; Hess, Tim M.; Knox, Jerry W. (Springer, 2014)
This paper reports on a study combining experimental field data with biophysical crop modelling to assess the impacts of irrigation heterogeneity on onion yield. The AquaCrop model was calibrated and validated for brown onion (cv Arthur) and used to simulate yield variability under a set of contrasting soil and agroclimatic conditions assuming perfect (100% uniform) irrigation. The impacts of non-uniform irrigation as measured on-farm under two overhead systems (mobile hose reel fitted with boom and a linear move) were then evaluated using scenario analysis and multi-model runs. Stochastic modelling confirmed that the lowest yield (8.6 t DM/ha) occurs on the lowest moisture retentive soils under the driest agroclimatic conditions with non-uniform irrigation. There is much greater yield variability in dry years compared to wet years. In wet years, rainfall reduces the scheduled number of irrigation events and buffers the effects of irrigation non-uniformity on yield. Yields were more variable under the mobile hose reel system fitted with the boom compared to the fixed linear move system. The modelled yield variability under non-uniform was similar to the observed yields reported by growers based on an industry survey. The study highlights the importance of achieving high irrigation uniformity in dry years on light soils to maximise yield and provides useful data for evaluating the potential yield benefits that might accrue from precision irrigation.